Pengaruh Variasi Fraksi volume dan Tekanan Terhadap Daya Serap Air Dengan Matrik PVA (Polivinil Asetat) - Arliansyah, Arul; Yuliyanto, Yuliyanto; Idiar, Idiar (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
Wood as the main raw material in making furniture causes the need for wood to increase while in its processing almost 30% of wood is wasted into waste just like that. In overcoming these problems, it is necessary to conduct research for the utilization of waste used for wood processing. Limited equipment in the manufacturing process becomes an obstacle to be one of the causes in the development of particle board products into a household industry. This research tried to make particle board with simple tools. This study used several parameters, namely 80:20, 70:30, 60:40, d and pressures of 7kg, 5kg, 3kg. The test results obtained the physical properties of wood dust composites with the Pva matrix, the lowest value was obtained at a variation of 80:20 pressure 7kg of 17.528% and the highest value at a variation of 60:40 pressure 7kg 117.237%. That the use of more matrices can inhibit water absorption is evidenced by micro photos at the 80:20 variation where the audience is no more than 25%. In the 60:40 variation, the use of more powder causes the glue bonding in this variation not to cover the powder as a whole like the 80:20 variation. Therefore, absorption at 60:40 is greater than at 80:20.